2019
DOI: 10.11648/j.ijefm.20190702.13
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Group Composition and Formalization on Financial Performance of Investment Groups in Kenya

Abstract: Investment groups are important for pooling of financial resources and lowering of investment risk. The issues, which affect their rates of return on investment, is however not fully known. The objective of the study was to analyze the effect of the group composition and group formalization on the financial performance of investment groups in Nakuru Town -Kenya. Descriptive survey design was used and stratified sampling technique was used to select a sample of 130 investment group members as well as investment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Studies have also focused on public debt dynamics and their implications for fiscal policy in Kenya. Kirui and Onyuma (2019) explored the determinants of public debt sustainability in Kenya, emphasizing the need for prudent debt management strategies. Kiamba et al (2020) assessed the impact of public debt on economic growth in Kenya and found evidence of a threshold level beyond which debt becomes detrimental to economic performance.…”
Section: Public Debtmentioning
confidence: 99%
“…Studies have also focused on public debt dynamics and their implications for fiscal policy in Kenya. Kirui and Onyuma (2019) explored the determinants of public debt sustainability in Kenya, emphasizing the need for prudent debt management strategies. Kiamba et al (2020) assessed the impact of public debt on economic growth in Kenya and found evidence of a threshold level beyond which debt becomes detrimental to economic performance.…”
Section: Public Debtmentioning
confidence: 99%
“…Studies also indicate that companies that have maintained gender diversity for about four to five years also significantly outperform those without female representation. Kirui and Onyuma (2019) note that the benefits of gender inclusivity extend beyond financial returns. The findings of Etiang (2020) suggest that there is a link between CSR and gender-inclusive leadership.…”
Section: Gender Mainstreamingmentioning
confidence: 99%
“…This involves deciding the amount to be invested in any particular financial security or asset, depending on the group objectives and the risk levels agreed on. For a start, investment groups usually invest in largely low risk to medium risk securities, as has been shown by Kirui & Onyuma (2019). As they grow they move into high risk investment portfolios.…”
Section: Conclusion and Policy Prescriptionmentioning
confidence: 99%